Answer:
F(10) = -25
Explanation:
To solve an explicit rule, we have to understand every terms in its formula. For a given equation,
F(n) = F(1) + d(n - 1)
Where F(n) = the nth term of the sequence
F(1) = first term
d = common difference
(n - 1) = one term less than the nth term
Note : the above explicit sequence is for arithmetic function.
From the above equation,
F(n) = F(10)
F(1) = 2
d = -3
(n - 1) = (n - 1)
To solve for the 10th term
F(10) = 2 + (-3)(10 - 1)
F(10) = 2 + (-3)(9)
F(10) = 2 + (-27)
F(10) = -25
The 10th term of the sequence is -25